Kesehatan Mental, Stres Kerja, dan Burnout Sebagai Isu K3 Di Indonesia: Tinjauan Literatur - Nurul 'Afifah Hijami (Health Research Journal of Indonesia, 2026)
Psychosocial risks in the workplace, such as high workload, role conflict, and low organizational support, are increasingly recognized as key determinants in occupational health and safety. Chronic exposure to these factors is associated with work-related stress, burnout, mental health problems, and reduced productivity and workplace safety. This review aims to analyze recent scientific evidence on work-related stress and burnout among workers and their impact on health and organizational performance. A literature review was conducted on articles published in Indonesian and English in peer reviewed journals over the past eight years. Included study designs comprised systematic reviews, meta-analyses, randomized controlled trials, cohort studies, cross-sectional studies, and qualitative studies measuring work-related stress, burnout, or psychosocial risks in occupational settings. The findings indicate a consistent association between psychosocial risks and increased levels of work-related stress and burnout across various sectors, including healthcare, transportation, construction, education, and industry. Reported impacts include mental health disorders, increased absenteeism, reduced productivity, and higher risk of occupational accidents. Multilevel organizational interventions demonstrate greater effectiveness compared with individual-based approaches alone. Work-related stress and burnout represent strategic issues in occupational health and safety. Integrating psychosocial risk management into organizational policies and practices is essential to protect workers’ health and maintain workplace safety and performance.